BAYI TABUNG DAN INSEMINASI BUATAN DALAM PERSPEKTIF SYAFII - Multazim Ahmadi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2016)
insemination is the reproductive process by incorporatingthe most good quality sperm into the uterus. To sort out thisexcellent sperm, the laboratory team who do the sorting. Spermwith good quality, judging from the quantity, which concentrateover 10 million per ml. Of 10 million per ml are prepared to getthe sperm actually qualified at least one million per ml. Thephenomenon of the birth of twins result of insemination happensabove shows that the current technology is progressing veryremarkable. And of course this is a fact that should be of concernto Muslims about their legal status. Because indirect artificialinsemination and IVF can be negative when the inseminationprocess was carried out by men and women who do not havevalid marriage relationship by religion. So the authors looked atthe importance of the problem of artificial insemination and IVFis peeled and discussed in this paper. While the Law of artificialinsemination and IVF process in tafsil as follows: if the sementube and inserted into the uterus of the woman is not marriedthen it is haraam. mani saved if the semen of husband and wifebut not how to remove it muhtaram then also haram. whensemen was deposited the semen of husband and wife and howto remove it included muhraram and inserted into the womb ofhis wife it is permissible.